Pattern of Urinary Stone Disease among Armed Forces Personnel - A Cross Sectional Study of 223 cases - Rakib, Md Abdur; Chowdhury, Md Ashif; Alam, Md Shafiul (Bangladesh Journal of Urology, 2023)
Introduction: Urinary stone disease is one of the common disease entities with higher male preponderance seen in urological practice. Though etiology of urinary stone disease is not well understood but some precipitating factors like urinary infection, less fluid intake, dietary habit and metabolic factors has been observed common among the members of Armed forces personnel. They are having common supplied food items with prolonged exposure to precipitating factors of stone formation. This observation leads to inference this study to see the distribution of urinary stones among the members of Armed forces personnel. Materials and Methods: This is a Cross-sectional study. A total of 223 patients diagnosed with urinary stone diseases and managed in Urology Center of Combined Military Hospital (CMH) Dhaka from 01 June 2022 to 30 June 2023 were included. The data was collected in a data collection sheet from hospital records. The data was entered into the Microsoft Excel software and analyzed using statistical package for social studies (SPSS) software 23.0 version. Results: Among 223 patients 182 patients were male and 41 were female and male female ratio was 4:1. Age range found from 8 years to 81 years, with a mean of 40.99 years. According to location of stone the most common site was ureter, followed by Kidney. The highest incidence of stone disease was found in the summer months (May - July). Conclusion: Urinary stones are predominantly found in male. Upper tract stone is more common than lower tract. During summer (May - July) more urinary stone disease found among armed forces personnel. Bangladesh J. Urol. 2023; 26(2): 104-109